Relative analytical sensitivity of donor nucleic acid amplification technology screening and diagnostic real‐time polymerase chain reaction assays for detection of Zika virus RNA. Issue 3 (14th February 2017) - Stone, Mars; Lanteri, Marion C.; Bakkour, Sonia; Deng, Xutao; Galel, Susan A.; Linnen, Jeffrey M.; Muñoz‐Jordán, Jorge L.; Lanciotti, Robert S.; Rios, Maria; Gallian, Pierre; Musso, Didier; Levi, José E.; et al.
Abstract : BACKGROUND: Zika virus (ZIKV) has spread rapidly in the Pacific and throughout the Americas and is associated with severe congenital and adult neurologic outcomes. Nucleic acid amplification technology (NAT) assays were developed for diagnostic applications and for blood donor screening on high‐throughput NAT systems. We distributed blinded panels to compare the analytical performance of blood screening relative to diagnostic NAT assays. STUDY DESIGN AND METHODS: A 25‐member, coded panel (11 half‐log dilutions of a 2013 French Polynesia ZIKV isolate and 2015 Brazilian donor plasma implicated in transfusion transmission, and 3 negative controls) was sent to 11 laboratories that performed 17 assays with 2 to 12 replicates per panel member. Results were analyzed for the percentage reactivity at each dilution and by probit analysis to estimate the 50% and 95% limits of detection (LOD50 and LOD95, respectively). RESULTS: Donor‐screening NAT assays that process approximately 500 µL of plasma into amplification reactions were comparable in sensitivity (LOD50 and LOD95, 2.5 and 15‐18 copies/mL) and were approximately 10‐fold to 100‐fold more sensitive than research laboratory‐developed and diagnostic reverse transcriptase‐polymerase chain reaction tests that process from 10 to 30 µL of plasma per amplification. Increasing sample input volume assayed with the Centers for Disease Control and Prevention reverse transcriptase‐polymerase chain reaction assays increased the LODs by 10‐fold to 30‐fold. CONCLUSIONS: Blood donor‐screening ZIKV NAT assays demonstrate similar excellent sensitivities to assays currently used for screening for transfusion‐transmitted viruses and are substantially more sensitive than most other laboratory‐developed and diagnostic ZIKV reverse transcriptase‐polymerase chain reaction assays. Enhancing sensitivities of laboratory‐developed and diagnostic assays may be achievable by increasing sample input.